The complete idiot's guide to personal bankruptcy - Epstein, Lita. (Indianapolis, IN : Alpha, 2010)
Provides financial advice and comprehensive information on all aspects of filing for personal bankruptcy, including the most current legal information with state-by-state exceptions and important websites to research before filing.
Includes index.
Keywords: Bankruptcy -- United States -- Popular works; Bankruptcy -- United States